Advances in Imaging Plant Cell Walls. (September 2019) - Zhao, Yuanyuan; Man, Yi; Wen, Jialong; Guo, Yayu; Lin, Jinxing
Abstract : Understanding of cell wall architecture, including the crosslinking of cell wall polymers, provides crucial information for elucidating the relationship between cell wall structure and cell function. Moreover, examination of the cell wall informs efforts to improve biomass breakdown in bioreactor conditions. Over the past decades, imaging techniques have been used extensively to reveal the structural organization and chemical composition of cell walls, but detailed imaging of the native composition and architecture of the cell wall remains challenging. Here, we review progress in the development of cell wall imaging techniques. In particular, we focus on several advanced, label-free techniques for imaging cell walls and their potential applications in investigation of the biological functions of plant cell walls. Highlights: Cell wall imaging can considerably permit direct visualization of the molecular architecture of cell walls and provide detailed chemical information on wall polymers, which is becoming one of the hot topics in contemporary botanical research. Label-free techniques based on Raman spectroscopic imaging, SRS in particular, can provide label-free dynamics and quantitative microanalysis of chemical compositions of living plant cell walls with a characteristic molecular vibration in situ, which has opened exciting new avenues for cell wall imaging Further studies integrating advanced label-free imaging techniques, using super-resolution microscopy, along with real-time studies of structural changes, will be conductive to refine current molecular organization and better understanding of cell wall architecture.